The strategic role of digital branding in enhancing the market value of Kapulaga through the DEKEGO web platform - Riana, Zenni; Fahmi, Nur Augus; Putra, Irwan Agusnu; Asmara, Muhammad Endang; Susilawati, Evi; Abdilah, Milwan; Sabila, Tasya Aliya; Zai, Elvan Dyan Lestari (Edelweiss Applied Science and Technology, 2025)
This study analyzes the role of digital branding in enhancing the market value of cardamom through the DEKEGO Web platform, which stands for Desa-desa Kecamatan Gomo (Village-to-Village of Gomo Subdistrict), located in South Nias Regency, North Sumatra, Indonesia. Digital branding is identified as the independent variable influencing consumer perception value as an intervening variable, which subsequently affects the market value of cardamom as the dependent variable. Using a quantitative approach, data were collected from 120 respondents representing cardamom SMEs in Gomo Subdistrict who utilize the DEKEGO platform. Questionnaires with a five-point Likert scale were analyzed using SmartPLS 4.0 to test both direct and indirect relationships. The results show that digital branding positively and significantly affects consumer perception value (β = 0.642; p < 0.001), which in turn enhances the market value of cardamom (β = 0.511; p < 0.001). The direct effect of digital branding on market value is also significant (β = 0.378; p < 0.01), with partial mediation by consumer perception value. The findings highlight that strengthening digital branding through interactive features, quality visual content, and platform optimization can improve competitiveness and selling price, offering practical insights for digital marketing in the agricultural sector.